Magnesium/silicon atomic weight percent ratio standards for the tissue identification of talc by scanning electron microscopy and energy dispersive X-ray analysis. (2nd November 2019) - McDonald, Sandra A.; Fan, Yuwei; Rogers, Rick A.; Godleski, John J.
ABSTRACT: Talc may lodge in human tissues through various routes, and has been associated with the development of ovarian carcinoma in case control epidemiologic studies. Talc is detected in tissues with scanning electron microscopy and energy dispersive X-ray analysis (SEM/EDS), with expected magnesium (Mg) and silicon (Si) peaks. The theoretical atomic weight % Mg/Si ratio for talc is 0.649, and for diagnostic purposes, a range of ± 5% (~0.617 to 0.681) is often used as a standard. Our goal was to establish empirically the quantitative range for talc identification by SEM/EDS using two source materials: a Johnson's Baby Powder TM (cosmetic-grade) consumer sample, and talc from Sigma-Aldrich (particle-grade material intended for scientific use). We examined 401 Mg-Si particles with SEM/EDS across the two samples, using two different SEM microscopes. Overall, we found a mean Mg/Si atomic weight % ratio of 0.645, with minimal differences between study subsets. The standard deviation was 0.025; (± 1σ = 0.620–0.670). The currently used ± 5% diagnostic range (Mg/Si 0.617–0.681) is thus reasonably close to this study's ± 1σ range, and well within a ± 2 σ confidence interval span (Mg/Si 0.595–0.695). The ± 5% range is thus an appropriately conservative standard whose continued use seems justified.